ANALISIS MOTIVASI BELAJAR PESERTA DIDIK BERDASARKAN PENERAPAN MODEL GAME BASED LEARNING DI KELAS III SDN KALIABANG TENGAH VII - Akbar, Ramdani Fauzidin; Hakim, Zerri Rahman; Rakhman, Patra Aghtiar (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2025)
This study aims to examine students’ learning motivation through the implementation of the Game-Based Learning model in Grade III at SDN Kaliabang Tengah VII. The research employed a qualitative descriptive method, with data collected through interviews, observations, and documentation. The findings reveal that appropriate lesson planning significantly contributes to achieving learning objectives aligned with students’ abilities. Students were actively engaged and showed high enthusiasm during mathematics lessons. The games designed were relevant to the learning objectives, enabling the teacher to create an enjoyable and interactive learning environment. The implementation of Game-Based Learning was proven to enhance students’ learning motivation based on several indicators, including diligence in completing tasks, persistence, confidence in expressing opinions, strong determination, and enjoyment in solving problems.